Does the size of the neuroendocrine-carcinoma component determine the prognosis of gallbladder cancer? - Hu, Ya-Fei; Wang, Jun-Ke; Ma, Wen-Jie; Hu, Hai-Jie; Gu, Han-Fei; Liu, Fei; Lv, Tian-Run; Yang, Si-Qi; Dai, Yu-Shi; Zou, Rui-Qi; Jin, Yan-Wen; Li, Fu-Yu (Frontiers in Endocrinology, 2024)
Gallbladder mixed neuroendocrine-non-neuroendocrine neoplasm generally consists of a gallbladder neuroendocrine tumor and a non-neuroendocrine component. The World Health Organization (WHO) in 2019 established a guideline requiring each component, both neuroendocrine and non-neuroendocrine, to account for a minimum of 30% of the tumor mass. Patients after surgery resection and diagnosed at microscopy evaluation with pure gallbladder neuroendocrine carcinoma (GBNEC), gallbladder mixed adeno-neuroendocrine carcinoma (GBMANEC, GBNEC≥30%), and gallbladder carcinoma mixed with a small fraction of GBNEC (GBNEC <30%) between 2010 and 2022 at West China Hospital of Sichuan University were collated for the analyses. Demographic features, surgical variables, and tumor characteristics were evaluated for association with patients’ overall and recurrence-free survival (OS and RFS). The study included 26 GBNEC, 11 GBMANEC, 4 gallbladder squamous-cell carcinoma (GBSCC), and 7 gallbladder adenocarcinoma (GBADC) mixed with a small fraction of GBNEC. All patients had stage III or higher tumors (AJCC8th edition). The majority of included patients (79.17%) underwent curative surgical resection (R0), with only ten patients having tumoral resection margins. In the analysis comparing patients with GBNEC percentage (GBNEC≥30% vs. GBNEC<30%), the basic demographics and tumor characteristics of most patients were comparable. The prognosis of these patients was also comparable, with a median OS of 23.65 months versus 20.40 months (P=0.13) and a median RFS of 17.1 months versus 12.3 months (P=0.24). However, patients with GBADC or GBSCC mixed with GBNEC <30% had a statistically significant decreased OS and RFS (both P<0.0001)) compared with GBNEC and GBMANEC. Patients with GBNEC who exhibited advanced tumor stages and lymphovascular invasion had a higher risk of experiencing worse overall survival (OS) and recurrence-free survival (RFS). However, a 30% GBNEC component was not identified as an independent risk factor. Patients with GBNEC were frequently diagnosed at advanced stages and their prognosis is poor. The 30% percentage of the GBNEC component is not related to the patient’s survival.